Constructing a desired image of China: Picture of territorial controversies in Chinese language textbooks - Wardęga, Joanna (Overcoming Controversies in East Asia, 2017)
China is one of the Asian countries, whose borders are contested by different actors on the geopolitical stage, who do not agree on the Chinese version of geography. As China is strengthening its soft power, one of the tools for the spreading of the Chinese version of the map of Asia are textbooks for teaching the Chinese language. Since 2004 China has been setting up Confucius Institutes around the world to spread its language and culture. There are some concerns and controversies arousing around Confucius Institutes, seen as Chinese government-backed institutions present on Western universities, and questions about their role in creating Chinese soft power. The purpose of this article is to understand one aspect of language education, that is how the Chinese territory is shown to the students of the Chinese language in the textbooks that are used in the Confucius Institutes.